Compatibility of the entomopathogenic fungi Metarhizium anisopliae e herbicides used in sugar cane crop / Compatibilidade do fungo entomopatogênico Metarhizium anisopliae e herbicidas utilizados na cultura da cana-de-açúcar - Rogério Teixeira Duarte; Luís Eugênio Lessa Bulhões; David Jossue López Espinosa; Karen Oliveira de Menezes; Aleska Batista da Silva; David Javier Matuz Zarate (Universidade Estadual de Alagoas, 2019)
: The aim of this work was analyze, in laboratorial conditions, the influence of active ingredients of herbicides used in sugar cane crop on the vegetative and reproductive development of the entomopathogenic fungi Metarhizium anisopliae. The active ingredients were diuron + sulfentrazone (5L * 100L-1) (Boral Duo® - FMC Chemical of Brazil Ltda.), clomazone (2L * 150L-1) (Gamit® - FMC Chemical of Brazil Ltda.) e tebuthiuron (2,4L * 300L-1) (Combine® - Dow Agrosciences Industrial Ltda.). The toxic effect of herbicides on the entomopathogen was performed in laboratorial conditions by addition the pesticides in culture medium BDA. After medium solidification were inoculated the reproductive structures of entomopathogen, at 107 conidia/mL, totaling eight replicates per treatment. After 24 h was analyzed the conidia viability, and after seven days were measured the area of colony growth (cm2), and counted the number of conidia for each treatment, being the media compared by Tukey test (P < 0.05), and standardized by compatibility classification. The active ingredient clomazone inhibited the vegetative growth and conidiogenesis of M. anisopliae, while diuron + sulfentrazone and tebuthiuron enable some development of entomopathogen. The greater viability was observed in the treatment with tebuthiuron, represented by 92.6 ± 1.12% of viable conidia, while diuron + sulfentrazone and clomazone were harmful. The active ingredients diuron + sulfentrazone and clomazone were toxic to M. anisopliae while tebuthiuron was classified like moderately toxic.